Corporate Social Responsibility in the Board Room: The Need for a Coherent Business Case. - Barratt, Ruth; Korac-Kakabadse, Nada; Barratt, Mark (Cranfield University, 2003)
Much has been made in recent years of the advantages to business of being a good corporate citizen; numerous studies now show a positive link between financial performance and ethical behavior. There is however little work which explores the role of the board and in particular how Non Executive or Outside Director (NEDs) affect corporate behavior. This study into the role and contribution of the Non Executive Director highlights an interesting dilemma; the majority of work in the boardroom is quantitative in nature. For many boardroom members especially those not working on a day to day basis within the organization, the very complexity of steering a large organization requires that data be presented in an easy to follow numerical format, and that a business case be established for individual projects. As a result of this NEDs are typically uncomfortable with the label CSR, which for them has connotations of simply “giving away profits”. Many NEDs in the study seemed to prefer the term “Corporate Responsibility” which for them implies a more reciprocal approach, whereby the organization establishes projects which then either directly or indirectly provide a straight forward return to the company for example; a company working in Africa establishes a number of HIV programs to ensure a healthy workforce, thereby lowering risk, and in doing so increases political support, raises worker moral and improves corporate reputation.